2021
DOI: 10.1002/ajoc.202100580
|View full text |Cite
|
Sign up to set email alerts
|

Iron(II)‐catalyzed Oxidative Coupling of Vicinal Diols and 2‐Amino‐1,4‐naphthoquinone for the Synthesis of Pyrrolonaphthoquinones and Furanonaphthoquinones

Abstract: Direct oxidative coupling of vicinal diols with 2aminonaphthoquinones has been studied for the selective synthesis of benzo[f]indole-4,9-diones at a moderate temperature. In the presence of an environmentally benign iron catalyst, the vicinal diols were oxidized to α-hydroxy carbonyl compounds. Subsequently, 2-amino naphthoquinone reacted with the resultant α-hydroxy carbonyl compound through tandem NÀ C and CÀ C bond formation to afford a vast range of pyrrolonaphthoquinones in remarkable yield. Interestingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…Furthermore, the synthesized C2-aminated naphthoquinones ( 1 – 15 , 18 – 27 , 43 – 47 ) could be utilized for the late-stage transformations, as several viable and practical synthetic routes have been reported for the transformation of synthesized C2-aminated naphthoquinones (Scheme ). …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the synthesized C2-aminated naphthoquinones ( 1 – 15 , 18 – 27 , 43 – 47 ) could be utilized for the late-stage transformations, as several viable and practical synthetic routes have been reported for the transformation of synthesized C2-aminated naphthoquinones (Scheme ). …”
Section: Resultsmentioning
confidence: 99%
“…Broggini’s group developed a method for synthesis of pyrroquinones through the process of Rh­(II)-catalyzed ring opening of 4-(1,4- naphthoquinone)-substituted isoxazolin-5-ones, decarbonation, and electrocyclic and reductive elimination. Panda’s group developed an Fe­(II)-catalyzed directly oxidative tandem reaction of vicinal diols with 2-aminonaphtho­quinones to construct pyrronaphtho­quinones. Maurya et al reported Rh­(II)-catalyzed coupling of α-azidochalcones with 2-hydroxy-1,4-naphtho-quinone under blue LED light.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, 2-substituted naphthoquinones were usually used as one of the materials to construct pyrroquinone derivatives through tandem cyclization reactions (Figure a). Representatively, Choudhury’s group reported an iodine-mediated three-component reaction of aryl methyl ketones or terminal aryl alkynes or arylglyoxal hydrate with barbituric acid and 2-aminonaphthoquinone for the synthesis of 2,3-disubstituted naphthoquinone-fused pyrroles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 With the availability of a great variety of synthetic methods, a few reports describe diols as attractive, eco-friendly, readily available and stable building blocks for the construction of regioisomerically pure pyrazoles (Scheme 1). 10 For example, Panda et al disclosed a seminal work on Fe( iii )-catalyzed regioselective synthesis of pyrazoles in the presence of an excess amount of diols. 10 a Later, they were able to synthesize substituted pyrazoles under neat conditions.…”
mentioning
confidence: 99%